ESTIMATION OF WILLINGNESS TO PAY TOWARDS RIVERSIDE LANDSCAPE DESIGN - Atrida Hadianti; Yoshiaki Kubota (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2019)
Riverside landscape design is developed not only to enhance amenity but also to address disaster risks. This study aims to estimate the value of the design of riverside landscape, in terms of amenity and disaster mitigation. Contingent valuation method (CVM) is used for valuation of the proposed design of riverside landscape. The case study was taken place in Yogyakarta City, Indonesia, that has three main rivers flowing through the city; Winongo River, Code River and Gajahwong River. As the rivers are headed from Merapi volcano, the community that occupied the riverside areas is threatened by the risks of cold pyroclastic debris flow, beside the regular riverine flood. Respondents are family representatives that chosen randomly from the total population of Yogyakarta City. There are 580 samples, consists of 333 samples of Type A and 247 samples of Type B. Visual image with explanation of amenity obtained higher WTP rather than with explanation of disaster mitigation indicates that the explanation of amenity features of the design is valued higher rather than disaster mitigation features. In addition, the value of extrapolated WTP results considerable amount in monetary term that represents the cost of realization of the design and also serves as feasibility of the project. However, visual image contain mixed value of the design to some extends, and the explanation increases the value of the design, due to the respondents may grasp other aspects than explained by viewing the visual image of the design. Reasons of willing to pay are all positively related to WTP, implies that people behaviour towards the riverside area is influencing the value, specifically related to their financial state. CVM as valuation technique for public good can be used to understand the perception and also to measure the acceptance of the public towards the proposed design.